Employee Compensation a Panacea for Increasing Workers Productivity: A Case Study of Benin Owena River Basin Development Authority - Daramola, Adedeji Adebola (International Journal of Business and Management Future, 2019)
Employees are a company’s livelihood. How they feel about the work they are doing and the results received from that work directly impact an organization’s performance and, ultimately, its stability. An unstable organization ultimately underperforms. The study had the following objectives: to establish the relationship between motivation and higher productivity among workers, to find out any relationship between motivational factors and work of staff and to determine how incentives influence workers approach to work and their performance. To achieve these goals, a questionnaire was designed based on the objectives. The completed questionnaires were processed and analyzed using the Simple Percentage. The findings of this study revealed that alongside monetary incentives, another key factor in motivating employees is to involve them in the process aimed at attaining organizational effectiveness because without their co-operation and support a great deal of managerial energy may be wasted. The study concluded that efforts should be aimed at motivating staff of all levels in order to increase productivity for higher returns. This study revealed that the higher motivation of workers leads to increasing productivity in BORBDA.